(untitled) (International Journal of Current Research in Physiology and Pharmacology, 2021)
Plant species belonging to the Ocimum genus are among the most popular medicinal plants and are being used for several purposes in ethnomedicine. Ocimum is universally cultivated however; the geographical distribution highlights three major centers of Ocimum diversity, these are: the tropical areas of America, the tropical region of Asia and the tropical and subtropical regions of Africa. Ocimum species have been employed traditionally for several medicinal purposes including antioxidant, antibacterial, hypoglycaemic, hepatoprotective, antiviral and other medicinal purposes. Though scientists have carried-out studies and chronicled the pharmacological potentials of Ocimum species, documents containing these data seem to be disassembled, making it difficult to really distinguish the pharmacologically useful species from those that are not and also to get comprehensive information about the medicinal species in this genus. Hence, the aim of this review is to outline classified information on the ethnopharmacology, phytochemistry and pharmacological importance of some Ocimum species that have been reported by different researchers. In carrying-out this review, the search for literature was done via relevant databases including PubMed, Springer, Web of Science, Science Direct, Embase, SciFinder, Google Scholar and Scopus. The species reviewed are the most widely used from the Ocimum genus in traditional medicine and they are also the most researched for intended use in conventional therapeutic practice. Literature reveals that these species contain several compounds which are responsible for the numerous pharmacological activities elicited by them including antimalarial, anticancer, antidiabetic, antiinflammatory and antioxidant effects.